Method of Teaching Students to Study the Electro physics Properties of Semiconductors and Mathematical Formula - Kasimakhunova Anarkhan Mamasadikovna; Atajonova Saidakhon Boratalievna (Genius Journals, 2022)
The article presents the results of theoretical prerequisites and the results of a study of the possibility of developing new teaching methods, using the theory of similarity based on everyday examples, especially for conducting classes in technical educational institutions.
Keywords: Teaching; technique; method; semiconductor